Effectiveness of Problem-Based and Project-Based Learning Models in Achieving Competencies in Database Learning - Dahri, Nuraeni; Mallisza, Danyl (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
This research aims to develop a Problem-Based and Project-Based Learning model to help students who struggle to achieve database learning competencies. This development research refers to the Research and Development method. The model's syntax consists of three stages-introductory, core, and concluding activities-implemented in six learning phases. A quasi-experimental design was conducted involving 30 students in the treatment and control groups. Statistical analysis showed that the Problem-Based and Project-Based Learning model significantly improved learning outcomes across cognitive (80.90 vs 65.93), affective (125.28 vs 85.13), and psychomotor (123.83 vs 95.40) domains, with a significance level of 95%. These findings highlight the effectiveness of Problem-Based and Project-Based Learning in overcoming learning difficulties, increasing learning motivation, and improving database project skills. Integrating problem-based and project-based learning can inform curriculum design, improve teaching strategies, and the results of this study can be used as evaluation material for teachers in choosing active learning approaches.